The Influence of Competence on Performance with Motivation as an Intervening Variable in General Hospitals - Maimunah; Rodhiah Rizki Amelia; Natalia Desi Puspitasari; Nursaid; Nurul Qomariah (IECON: International Economics and Business Conference, 2024)
Performance is an important thing that must always be considered by every organizational implementer. Organizational leaders must strive so that employee performance must achieve targets in accordance with previously planned targets. The purpose of this study is to determine the impact of competence on employee performance with motivation as an intervening variable with  at a government-owned general hospital operating in the city of Bondowoso. Variables in this study is independent variable (competence) and the dependent variable (employee performance). The analysis used is descriptive analysis with 100 samples respondents. The results of the analysis show that competence and work motivation have a positive impact on employee performance. For the indirect effect of competence on performance through motivation, it also has a positive and significant effect.